Antioxidant potential of indigenous cyanobacterial strains in relation with their phenolic and flavonoid contents. Issue 11 (2nd June 2016) - Ijaz, Saadia; Hasnain, Shahida
Abstract: Antioxidant activities of eight indigenous cyanobacterial strains belonging to the genera Oscillatoria, Chroococcidiopsis, Leptolyngbya, Calothrix, Nostoc and Phormidium were studied in relation with their phenolic and flavonoid contents, ranging 3.9–12.6 mg GAE g −1 and 1.7–3.44 mg RE g −1 . The highest activities were shown by Leptolyngbya sp. SI - SM (EC50 = 63.45 and 67.49 μg mL −1 ) and Calothrix sp. SI - SV (EC50 = 65.79 and 69.38 μg mL −1 ) calculated with ABTS and DPPH assays. Significant negative correlations were seen between total phenolic and flavonoid contents and the antioxidant activities in terms of EC50 values. Furthermore, HPLC detected 15 phenolic compounds with total concentrations ranging from 277.3 to 829.7 μg g −1 . The prevalent compounds in most of the strains were rutin, tannic acid, orcinol, phloroglucinol and protocatechuic acid. Cyanobacterial strains showed high potential as a good source of phenolic compounds with potent antioxidative potential which could be beneficial for food, cosmetic and pharmaceutical industries. Abstract :